DEVELOPMENT OF AGRICULTURAL BUSINESS IN INCREASING THE CULTIVATION OF ARABICA COFFEE PLANTS (Coffea arabica L) IN MANDAILING NATAL REGENCY : PENGEMBANGAN USAHA TANI DALAM PENINGKATAN BUDIDAYA TANAMAN KOPI ARABIKA (Coffea arabica L) DI KABUPATEN MANDAILING NATAL - Wahyudi, Rizky (UPMI Proceeding Series, 2023)
Coffee is Wrong One results commodity owned plantation _ mark economical enough _ tall between plant plantation other And role important as source state foreign exchange . No coffee only role important as source foreign exchange but Also is source income for No not enough from One half million soul coffee farmers in Indonesia . The method used in this study is the method of evaluating land suitability and evaluating coffee cultivation farmers. From the results of the study there are several problem factors faced by farmers such as the lack of optimal land management. With this evaluation, solutions to increase coffee plant production can be implemented.